Requirements for technical and financial assistance to improve regional competitiveness: the agricultural sector: paper for panel discussion - Sankar, Beni (CCS GeorgetownGY, 1993)
Identifies the components of the agricultural sector in Guyana. Highlights the rice industry and examines the constraints found in the industry by looking at the areas of production, marketing and institutional support services. Indicates some of the barriers affecting regional trade.